2009
DOI: 10.1080/13803390902858874
|View full text |Cite
|
Sign up to set email alerts
|

Executive dysfunction in traumatic brain injury: The effects of injury severity and effort on the Wisconsin Card Sorting Test

Abstract: This study examined the persistent effects of traumatic brain injury (TBI) on Wisconsin Card Sorting Test (WCST) performance. Since poor effort can contaminate results in populations with incentive to perform poorly, performance validity was explicitly assessed and controlled for using multiple well-validated cognitive malingering indicators. Participants were 109 patients with mild TBI and 67 patients with moderate-to-severe TBI seen for neuropsychological evaluation at least one year post injury. Patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
26
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 59 publications
4
26
0
2
Order By: Relevance
“…Nevertheless, our findings showing TBI-induced deficits in attentional performance at more severe levels of injury severity (2.8 and 3.0 mm impact depth), but not at milder levels (2.6 mm), are in accord with clinical studies reporting no significant changes in WCST perseverative responses after mild TBI, 61 as well as no measurable deficits in overall WCST performance in a subsequent study, where only patients with moderate-to-severe TBI showed larger deficits on several WCST indices at approximately 2.5-3.5 years postinjury. 23 The time interval between head trauma and EF assessment in these studies is comparable to the one implemented in the current study (i.e., 4 weeks postinjury), considering that, during adulthood, each rat month is approximately equivalent to 2.5 human years. 62,63 All rats in the control groups successfully completed training and testing procedures, whereas in groups subjected to injury, 2 rats were eliminated because they did not complete training and 3 more did not complete the behavioral test procedure (1 in the TBI [2.6 mm] group, 2 in the TBI [2.8 mm] group, and 2 more in the TBI [3.0 mm] group).…”
supporting
confidence: 48%
See 2 more Smart Citations
“…Nevertheless, our findings showing TBI-induced deficits in attentional performance at more severe levels of injury severity (2.8 and 3.0 mm impact depth), but not at milder levels (2.6 mm), are in accord with clinical studies reporting no significant changes in WCST perseverative responses after mild TBI, 61 as well as no measurable deficits in overall WCST performance in a subsequent study, where only patients with moderate-to-severe TBI showed larger deficits on several WCST indices at approximately 2.5-3.5 years postinjury. 23 The time interval between head trauma and EF assessment in these studies is comparable to the one implemented in the current study (i.e., 4 weeks postinjury), considering that, during adulthood, each rat month is approximately equivalent to 2.5 human years. 62,63 All rats in the control groups successfully completed training and testing procedures, whereas in groups subjected to injury, 2 rats were eliminated because they did not complete training and 3 more did not complete the behavioral test procedure (1 in the TBI [2.6 mm] group, 2 in the TBI [2.8 mm] group, and 2 more in the TBI [3.0 mm] group).…”
supporting
confidence: 48%
“…20 In humans, the Wisconsin Card Sorting Test (WCST) has been successfully employed as a well-validated neuropsychological measure of complex cognitive processes and was shown to sensitively characterize strategyswitching impairments in patients with TBI, [21][22][23][24] depression, and other neuropsychiatric disorders thought to affect the prefrontal cortex. [25][26][27] To specifically explore the different facets of behavioral flexibility assessed in the WCST, Birrell and Brown developed an analogous behavioral test to measure attentional setshifting performance in rats and demonstrated a pivotal role played by the rodent prefrontal cortex (PFC) in mediating complex cognitive processes in this test, such as attentional set-shifting 28 and stimulus reversal learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of mTBI, it is has been suggested that premorbid variables or psychological reactions may be more important because the sequelae often exceed what would be expected on the basis of the assumed injury. [15][16][17] Specifically, it is thought that pre-existing problems, 18 inflated recollections of premorbid ability (''good-old-days'' phenomenon), 18,19 diagnosis threat (poor performance resulting from expectations associated with a particular diagnosis), 6,20 stereotype threat (poor performance resulting from the pressure to perform at preinjury levels), 21 and/or disingenuous effort, 22 possibly motivated by financial compensation, 23 may contribute to poor outcomes after mTBI. Moreover, the fact that many symptoms are not specific to TBI has led to the suggestion that they may be better explained by other factors, such as depression and post-traumatic stress, 24 involvement in litigation, 19,25 or the stress associated with litigation.…”
Section: Introductionmentioning
confidence: 99%
“…We chose for this purpose the Wisconsin Card Sorting Test (WCST) 21 because it is widely used and has been previously validated as being sensitive to severity of TBI. 22,23 In the single previous study that explored findings and correlates of the BRIEF-A in a sample with moderate-severe TBI, no statistically significant correlations with performance on the WCST were found. 13 However, that finding has not yet been replicated and the association between the BRIEF-A and the WCST has also not yet been explored in mild TBI.…”
mentioning
confidence: 57%